The Role of Big Five Personality in Intimacy of Romantic Relationship - Rachmawati, Dwi Putri Ayu; Tobing, David Hizkia (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 2 (2021): Volume 1 Nomor 2 Tahun 2021 - Widya Cakra, 2021)
Intimacy is a core component in every relationship, especially in a romantic relationship which serves as the foundation of love, an important pillar of a healthy relationship, and the root of relationship satisfaction. When choosing a life partner, personality is one of the factors to consider because it’s closely related to an individual’s conflict resolution style and is also indicated to affect an individual's ability to form an intimate relationship with their partner. The research aimed to discover the role of Big Five personality (extraversion, agreeableness, conscientiousness, emotional stability, intellect) towards intimacy in romantic relationship. The respondents of this study were between 16 to 34 years old, high school graduate or student, and currently having romantic relationships (dating) in Indonesia (N = 175). Big Five personality is measured by International Personality Item Pool-Big Five Factor Marker (IPIP-BFM-50 Indonesia) and intimacy is measured by intimacy subscale of Triangular Love Scale (TLS). The results of multiple regression analysis using the bootstrap method with 1000 samples show that Big Five personality did not have a significant role towards intimacy in romantic relationships altogether. In addition, extraversion, agreeableness, conscientiousness, emotional stability, intellect each did not have a significant role towards intimacy in romantic relationship.